ADVANTAGES AND DISADVANTAGES OF IMPLEMENTATION OF KOREAN EDUCATIONAL SYSTEM IN UZBEKISTAN - Omonullo, Khamdamov; Dinara, Adbikarimova; Nasiba, Sherkuzieva; Nargiza, Tursunova (International Journal of Psychosocial Rehabilitation, 2020)
Needless to say, one of the most important factors in the development of a certain country is education, because South Korea has already proved this statement. Although the country has a few natural resources, they have achieved great development in almost all spheres, especially, in terms of education. Several countries are using the experience of this country, assuming they will boost their economy relying on success factors of South Korea. The Republic of Uzbekistan is also going to implement some successful methods in the educational systems of abovementioned countries. This paper studies the system of education of South Korea, and compares the pros and cons of its implementation in Uzbekistan.